Growth and production of lettuce on substrates based on detritivorous earthworms drilocomposts - Ferreira Rocha, Josilene; Ferreira Kusdra, Jorge; de Lima Moreno, Andréia; Coutinho Picazevicz, Angelita Aparecida (Comunicata Scientiae, 2022)
Alternative plant growing inputs have been increasingly sought out to reduce the economic-environmental impacts of intensive use of synthetic fertilizers in conventional agriculture. This study aimed to evaluate the production components of lettuce in response to the use of earthworm compost in substrate compositions. The experiment was carried out in a greenhouse using a completely randomized design in a 3 x 5 factorial scheme, with six replications, testing three earthworm species (Eisenia andrei, Eudrilus eugeniae, and Perionyx excavatus) and five drilocompost ratios (0%, 25%, 50%, 75%, and 100%), produced by these species and added to the composition of substrates by mixing them with soil. Production components evaluated comprised total and commercial numbers of leaves, commercial fresh weight, as well as shoot and total fresh and dry weights. Lettuce production components increased as the drilocompost ratio in substrates was raised, regardless of the earthworm species. Moreover, the addition of 25% this drilocomposted material in the dystrophic soil was enough to improve its fertility condition. In general, substrates prepared with worm castings from Perionyx excavatus and Eudrilus eugeniae were more efficient in increasing lettuce production components than that from Eisenia andrei.